1989
DOI: 10.1007/bf03350056
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thyroxine metabolism in hexachlorobenzene-intoxicated rats

Abstract: The effect of hexachlorobenzene (HCB) (1 g/kg bw) administration for 4 weeks, on thyroxine (T4) and triiodothyronine (T3) metabolism was studied in Wistar rats. The effect on serum binding of T4 has also been studied. Animals were injected with a tracer dose of either labeled hormone and by examining serum L-125I-T4 and L-125-I-T3, kinetics of radiolabeled hormones metabolism were calculated. The T4 metabolic clearance (MCI) as well as the distribution space, were increased by 6 fold. Decreased serum T4 levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Increased liver/body weight is a well-known effect of HCB in chronically intoxicated rats, as was demonstrated in our laboratory. 18,19 The present investigation is the first to demonstrate that long-term HCB (1 g kg Ϫ1 body wt.) administration induced alterations in the female Wistar rat oestrus cycle characteristics, resulting in irregularity of cycles, characterized mainly as prolonged periods of oestrus.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Increased liver/body weight is a well-known effect of HCB in chronically intoxicated rats, as was demonstrated in our laboratory. 18,19 The present investigation is the first to demonstrate that long-term HCB (1 g kg Ϫ1 body wt.) administration induced alterations in the female Wistar rat oestrus cycle characteristics, resulting in irregularity of cycles, characterized mainly as prolonged periods of oestrus.…”
Section: Discussionmentioning
confidence: 57%
“…This dose was previously used in our and other's laboratories to induce hepatic porphyria and liver lipogenic enzymes and to study thyroid status. 18,19 Treatment with HCB had no effect on the general health of the animals, as shown by the healthy appearance of the rats, and no effect on body weight or water and food consumption. After 2 weeks of HCB administration, the cycles were observed again until the day of sacrifice, i.e.…”
Section: Experimental Designmentioning
confidence: 95%
“…These results are consistent with those of previous studies in which male or female rats were treated with HCB for various periods of time (van Raaij et al, 1991;Foster et al, 1993;van Raaij et al, 1993a). The decrease in serum TT4 concentrations achieved by repeat administrations of HCB may be due to competitive interactions between the major metabolite pentachlorophenol (PCP) and hormone serum-binding proteins (van Raaij et al, 1991) and to increases in the rate of metabolism of T4 (Kleiman de Pisarev et al, 1989), which is the main known cause of decreases in serum TT4 levels. HCB may, in addition to binding to the T4 receptor, also modulate levels of the unidentified nuclear proteins that bind to the thyroid hormone response element (Loaiza-Perez et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of HCB poisoning include the disturbance of thyroid hormone homeostasis (Rozman et al, 1986;Kleiman de Pisarev et al, 1989;van Raaij et al, 1993a). HCB decreases thyroid hormone concentrations by increasing glucuronidation and inhibiting type-1 iodothyronine deiodinase activities (van Raaij et al, 1993b;Visser et al, 1993), interfering with the serum carrier binding of thyroid hormones (van Raaij et al, 1991) and increasing thyroid-stimulating hormone concentrations (van Raaij et al, 1993a).…”
Section: Introductionmentioning
confidence: 98%
“…Numerous animal studies have demonstrated HCB-induced hypothyroidism, with T 4 levels being particularly sensitive in rats (Alvarez et al 2005; Foster et al 1993; Kleiman de Pisarev et al 1990, 1995; Rozman et al 1986; van Raaij et al 1993). Lower T 4 levels associated with HCB exposure may be attributed to peripheral disposition of T 4 (Kleiman de Pisarev et al 1989) or increased hepatic T 4 metabolism (Kleiman de Pisarev et al 1990). It has also been suggested that HCB affects the thyroid in rats via its metabolites, particularly the main metabolite pentachlorophenol, an effective competitor for T 4 binding sites (van Raaij et al 1991a, 1991b).…”
Section: Discussionmentioning
confidence: 99%